Influencing ESG perception in SMEs through CSR, business ethics, and HRM: An empirical study in V4 countries - Jaroslav Belas; Adam P. Balcerzak; Jan Dvorsky; Justas Streimikis (Amfiteatru Economic Journal, 2024)
The aim of the paper is to define the important factors of Corporate Social Responsibility (CSR), Business Ethics (BE), and Human Resource Management (HRM), and to quantify their impact on the formation of positive attitudes of SMEs towards the concept of Environmental, Social, Governance (ESG) and its acceptance. To support the achievement of this goal, empirical research was conducted in the Visegrad Group (V4 countries) with a sample of 1,056 respondents in March 2024. The defined scientific hypotheses were verified through the Ordered Least Model (OLM). The research results indicate the following trends. Selected factors from CSR, BE, and HRM demonstrated an influence on shaping the positive attitudes of SMEs toward understanding and accepting the ESG concept. Empirical research confirmed that the CSR domain significantly influences the positive approach of SMEs towards ESG. This study in the HRM field emphasises the importance of a participatory leadership style for employees. This approach, among other benefits, contributes to a positive attitude of SMEs towards understanding and accepting the ESG concept. Planning the qualification and career growth of employees does not represent significant factors in shaping the positive stance of SMEs towards ESG. SMEs attitudes in the BE field clearly indicate that a consistent approach by managers in implementing anti-corruption measures shapes the right approaches of SMEs towards ESG. On the other hand, the formal declaration of applying BE in the activities of SMEs and the existence of a moral code do not positively influence the perception on ESG.
Keywords: L26; A13; M14; 330; business ethics; corporate social responsibility; environmental social governance; human resources management; small and medium-sized enterprises